InGaN/GaN light-emitting diodes : from modeling to their hybrid applications with novel nanomaterials - Hasanov, Namig (2017)
In last two decades, InGaN/GaN light-emitting diodes have been one of the main focus of research thanks to their low power consumption, high efficiency, long lifetime, high color purity and color quality, narrow luminescence, possibility to tune the emission wavelength from near ultraviolet to green by increasing the In content, and several other promising properties. In early stages of the development of InGaN-based LEDs, growing high quality epitaxial films on a suitable substrate was the main issue. This issue was effectively bypassed by growing the main device layers on the lattice-matched buffer layer. Another big issue was the difficulty to achieve high p-type conductivity in GaN; the problem was solved by high temperature annealing and low energy electron beam irradiation methods. In order to achieve a well operating InGaN/GaN light-emitting diode, both optical and electrical properties should be in the desired level. The main performance measure of these devices is the external quantum efficiency. To increase the external quantum efficiency, the issues with the carrier injection, radiative recombination, light-extraction, ohmic contacts, and several other factors that limit the overall performance of the device need to be properly addressed. Although InGaN-based light emitting diodes have been strongly developed, the performance of the devices still needs to be increased by novel methods. Moreover, the devices need to be properly characterized in both wafer-level and chip-level states to deeply investigate the drawbacks and advantages of each element during the growth and fabrication. Furthermore, the applications of light emitting diodes needs to be extensively investigated which can be realized through making hybrid systems and combining the advantages of these light emitting devises and novel materials. Although, there are some studies on this kind of hybrid applications, there is still a long way to go to make use of InGaN/GaN light emitting diode structures in pumping novel materials and devices. In this thesis, we systematically investigate the design, growth, wafer-level characterization, device fabrication, and device-level characterization of InGaN/GaN light-emitting diode structures grown on polar sapphire substrates. We demonstrate optimized growth process and wafer-level characterization of high crystal quality InGaN/GaN device. The fabrication and device-level characterization of improved conventional, flip-chip and vertical light-emitting diodes are demonstrated following the growth of the epitaxial layers. Next, we investigate the advantages and drawbacks of Ni/Ag/Ni/Au and Ni/Ag/Ti/Au ohmic reflectors and compare the devices fabricated with both types of the contact-mirrors. The proposed device outperforms the reference device in terms of electrical (lower forward voltage) and optical properties (higher reflectance). Moreover, the critical role of the incorporation of sputtered TiW was studied and it was concluded that the TiW-incorporated light-emitting diodes exhibit higher light extraction, higher optical power, and higher external quantum efficiency compared with those without TiW. The enhancement in the device performance was mainly attributed to the robustness of the device against high temperature annealing. Electroluminescence measurements further confirmed that TiW-incorporated light emitting diodes possess better heat management. We also investigated the critical role of InGaN epitaxial thin layer on the electrical performance of the device. By testing the layers with several thicknesses and In compositions, we came to the conclusion that a 2 nm thick InGaN layer with high In composition can enhance the current-voltage characteristics of the device by creating a 2-dimensional hole gas in the interface. The generation of holes in the interface is attributed to band bending induced by the piezoelectric polarization owing to the lattice mismatch. We investigated the effect of grading the InGaN quantum wells along the growth directions and compared the carrier distribution, radiative recombination rate, optical power, and external quantum efficiency with those of the conventional structure device. Moreover, we performed extensive study on the thickness-dependent performance enhancement of the quantum wells and concluded that the device with 6.5 nm thick graded quantum wells outperforms the conventional device with 2.5 nm thick quantum wells. Furthermore, studies also showed that having only three graded quantum wells with 6.5 nm thickness in the active region is more effective than having eight non-graded 2.5 nm thick quantum wells. Quantum confined stark effect is a well-known phenomenon which strongly reduces the performance of the devices owing to the separation of charge carriers due to the piezoelectric polarization induced-band bending. This bending in both conduction and valence bands strongly affects the carrier transport. The bending reduces effective barrier height of AlGaN electron blocking layer for electrons and increases barrier height for holes. Bearing in mind the low mobility and concentration of holes and the leakage of electrons, we introduced two additional InGaN quantum wells in the electron blocking layer to recycle the leaked electrons. The radiative recombination was significantly increased which was consistent with optical power and external quantum efficiency results. Moreover, we showed that, by having only six quantum wells in the active region and two quantum wells within the electron blocking layer can still significantly increase the performance of the conventional device with eight quantum wells. The synthesis of novel nanomaterials and their hybridization with optoelectronic materials and devices have recently become one the main research areas which combines the electrical injection properties of the one and the optical, structural, and geometrical properties of another material. In that manner, we chemically synthesized novel 2D CdSe nanoplatelets, and performed optical and morphological characterization. Moreover, we increased the photoluminescence of CdSe solid films with the incorporation of localized surface plasmons. The photoluminescence enhancement was attributed to the electric field enhancement and increased number of radiative channels in the presence of metallic nanoparticles, which was also confirmed with theoretical studies and time-resolved photoluminescence spectroscopy experiments. We believe this method will be useful in devices incorporating CdSe nanoplatelets as main active materials. Moreover, we investigated the critical role of CdSe nanoplatelets in the performance of color-converted InGaN/GaN light-emitting diodes as an exciton donor for the color converter CdSe/ZnS nanocrystal quantum dots. The hybrid device fabricated with the CdSe nanoplatelets outperformed the one without the nanoplatelets in terms of power conversion efficiency. The enhancement was ascribed to the exciton migration from donor CdSe nanoplatelets to acceptor CdSe/ZnS quantum dots both of which were pumped with InGaN/GaN light-emitting diode. Nonradiative Forster-type excitonic energy transfer between these donor-acceptor pairs was further confirmed with time-resolved photoluminescence spectroscopy and photoluminescence excitation measurements. Furthermore, we investigated Forster resonance energy transfer to CdSe nanoplatelets from InGaN quantum wells of bulk and nanopillar structures. Optical characterization revealed that the internal quantum efficiency and light extraction efficiency of nanopillar device structure were higher than those of the as-grown structure owing to the increased surface to volume ratio and the strain-relaxation. Next, the excitonic energy transfer between InGaN/GaN nanopillars and chemically synthesized CdSe nanoplatelets were monitored with time-resolved photoluminescence decay measurements. Resonance energy transfer from bulk quantum well capped with 3 nm GaN cap layer was also investigated in a similar manner following short characterization of bulk quantum well epitaxial structure. The energy transfer efficiency of the bulk quantum well system was higher than that of the nanopillar structure. The enhanced exciton migration was attributed to the reduced separation between the quantum wells and the nanoplatelets in the bulk quantum well structure compared with the nanopillar structure. Stacking of nanoplatelets is believed to strongly reduce the chance of nanoplatelets to be in the close proximity of the quantum wells in the InGaN/GaN nanopillar arrays. In summary, the thesis includes the epitaxial growth, device fabrication, wafer-level and device-level characterization, studies of novel device designs, and hybrid applications of InGaN/GaN light-emitting diodes structures with novel CdSe nanoplatelets. Effective methods to increase the electrical and optical performance of the device were discussed in detail and the performance of the devices was compared with the conventional structures. The thesis work has provided important insights for design, growth, fabrication, characterization, and applications of high performance InGaN/GaN light-emitting diodes and heterostructures.